Visitor management in tourism destinations - Albrecht, Julia N. (CABI Series in Tourism Management Research, 2017)
This book considers visitor management (VM) as a component of destination management at all levels of a destination and involving a wide range of stakeholders. It aims to demonstrate current knowledge on VM and to provide insights into conceptual issues rather than providing merely descriptive case studies. This book is primarily aimed at postgraduate students and researchers. The introduction and foundation chapters in Part I provide the context for the book as well as the broader topic of VM. Part II considers critical concepts in VM (indicators and standards-based VM frameworks, VM and service quality and visitor affinity) while Part III illustrates current issues in VM (visitor monitoring, tourist behaviour and vandalism, and the use of technology). Part IV of the book addresses guiding and interpretation, and their roles and relevance in VM. The book has 15 chapters and a subject index.